Residual nitrogen from slurry and mineral fertiliser two years after application: Fractionation and plant availability. (February 2023) - Fuchs, Max; Frick, Hanna; Moinet, Gabriel Y.K.; Mayer, Marius; Bünemann, Else Katrin
Abstract: Fertilisation with animal manure has a long-standing tradition as a way to close nutrient cycles on farms. However, the fate of nitrogen (N) from manure in the soil beyond the year of application remains poorly understood. The aim of this research was to understand the residual N fertiliser value of mineral fertiliser (Min) and cattle slurry (Slu) in relation to the partitioning of N from the fertilisers in different soil physical fractions. To this end, we characterised the fate of 15 N-labelled Min and Slu in soil organic matter (SOM) physical fractions two years after field application and related it to plant uptake of residual N. A secondary objective was to compare two fractionation methods with respect to accuracy and easiness, namely a combined density and particle size fractionation, separating five fractions, and a simple particle size fractionation, separating two fractions. All fractions were analysed for 15 N abundance. The residual N fertiliser value was determined as the uptake of 15 N by ryegrass ( Lolium multiflorum ) during 6 weeks. Furthermore, we deduced the source of 15 N taken up by the plants from changes in the percentage of N derived from labelled fertilisers in each of the SOM physical fractions obtained by simple size fractionation before and after the pot experiment. Two years after application, most 15 N was found in the fractions <20 μm, for both fractionation methods, i.e. in the mineral-associated organic matter (MAOM). The 15 N recovery in these fractions in percent of the quantity of 15 N originally applied as fertiliser tended to be higher for Slu (density-size fractionation: 19.8 ± 6.6%; simple size fractionation: 25.1 ± 6.6%) than for Min (density-size fractionation: 12.0 ± 2.1%; simple size fractionation: 16.8 ± 2.6%). Irrespective of the fertiliser type, about 2% of applied 15 N was available to ryegrass plants two years after application. Out of these 2%, most 15 N in the plants originated from MAOM, suggesting that the availability of the N stored in MAOM could be larger than previously thought. This finding is in line with the emerging view that MAOM is a dynamic fraction that plays an important role in the N cycle. Highlights: Residual 15 N from fertilisers after two years mostly in the <20 μm SOM fractions. 15 N recovery in soil greater for cattle slurry than for mineral fertiliser. Ryegrass grown for 6 weeks recovered around 2% of 15 N applied 2 years earlier. Most 15 N taken up by the ryegrass plants was derived from MAOM. SOM fractionation methods differed in 15 N losses.